Analisis Kinerja Web Server Menggunakan Algoritma Round Robin dan Least Connection - Molavi Arman; Novan Wijaya; Hafiz Irsyad (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2017)
In the industrialized world many companies are using web as a form of promotion or online transactions such as e-commerce. It handles millions of hit visits on the web server. There are many things that can cause the failure hit. One of them is the number of requests or transactions to the web server that is not able to be handled or the slowness of the response, which is very dangerous and detrimental for the company. The single web server with extremely expensive brands is a way to face the constraints overload, but only certain companies are able to have it. The issues faced, how to use some of the PCs as a web server with a reasonable economic value, could be empowered by implementing network load balancing technology. Network load balancing is a technology solution that is used, and expected to be able to handle the simultaneous load of web server with small output failure. Web server performance measurement at the round robin algorithm and least connection include parameters against components such as throughput, request loss, response time and cpu utilization, from the result of the measurement, it will be seen which is the best algorithm to use.